2014
DOI: 10.1186/1745-6215-15-141
|View full text |Cite
|
Sign up to set email alerts
|

‘Putting Life in Years’ (PLINY) telephone friendship groups research study: pilot randomised controlled trial

Abstract: BackgroundLoneliness in older people is associated with poor health-related quality of life (HRQoL). We undertook a parallel-group randomised controlled trial to evaluate the effectiveness and cost-effectiveness of telephone befriending for the maintenance of HRQoL in older people. An internal pilot tested the feasibility of the trial and intervention.MethodsParticipants aged >74 years, with good cognitive function, living independently in one UK city were recruited through general practices and other sources,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(50 citation statements)
references
References 47 publications
0
50
0
Order By: Relevance
“…All studies identified a primary outcome which included measures across depression, 14–16 19 23 25 social support, 17 18 27 social network, 26 mental well-being, 20 quality of life 21 24 and social functioning 22 ( table 2 ). There were eight patient-reported outcomes, five clinician-reported outcomes and one study that included both patient and clinician-reported outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…All studies identified a primary outcome which included measures across depression, 14–16 19 23 25 social support, 17 18 27 social network, 26 mental well-being, 20 quality of life 21 24 and social functioning 22 ( table 2 ). There were eight patient-reported outcomes, five clinician-reported outcomes and one study that included both patient and clinician-reported outcomes.…”
Section: Resultsmentioning
confidence: 99%
“…These type of programs designed specifically for older adults show positive effects on sense of wellbeing and social engagement (Ballesteros et al, 2014b;Pao, 2014). Technology-based studies such as teleconferencing were the channel used by trained volunteers with urban elders recruited from primary care practices (Mountain et al, 2014). This pilot RCT study aimed to recruit individuals aged 74+ with a good cognitive function and living independently in order to establish whether a home-based intervention set up on telephone communication delivered through trained volunteers could improve or successfully maintain mental wellbeing of older people who were vulnerable and hard to reach.…”
Section: Intervention Studiesmentioning
confidence: 99%
“…We compared 10 models using four example case studies from iRCTs with clustering in one arm: specialist clinics for the treatment of venous leg ulcers [15], acupuncture for low back pain [7], cost-effectiveness of community postnatal support workers (CPSW) [16], and Putting Life in Years (PLINY) [17]. These studies were selected from our portfolio of studies as trial statisticians that had clustering in one arm only.…”
Section: Modelsmentioning
confidence: 99%